Pengaruh Status Kepegawaian dan Kompetensi Pegawai Terhadap Motivasi Kerja Pegawai: (Studi Kasus pada Dinas Pertanian Kabupaten Pangandaran) - Ivi Yulianti; Ading Rahman Sukmara (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study was initiated because of the problem of decreasing employee work motivation. So the purpose of this study is to determine and analyze the effect of employee status on employee work motivation at the Pangandaran Regency Agriculture Service. To determine and analyze the effect of employee status and employee competence on employee work motivation at the Pangandaran Regency Agriculture Service, the method used in this study is quantitative descriptive research. Based on the results of the research and discussion, the following conclusions are obtained. Employee status has a positive and significant effect on employee work motivation at the Pangandaran Regency Agriculture Service. This shows that if employee status increases, employee work motivation at the Pangandaran Regency Agriculture Service will increase. Employee competence has a positive and significant effect on employee work motivation at the Pangandaran Regency Agriculture Service. This shows that if employee competence continues to increase, employee work motivation at the Pangandaran Regency Agriculture Service will increase. Employee status and employee competence have a positive and significant effect on employee work motivation at the Pangandaran Regency Agriculture Service. If the employee status and employee competency are implemented properly, then employee work motivation at the Pangandaran Regency Agriculture Service will increase.